Hubble Tarantula Treasury Project V. The Star Cluster Hodge 301: the old face of 30 Doradus - Cignoni, Michele; Grebel, Eva K.; Gouliermis, Dimitrios A.; Panagia, Nino (The astrophysical journal, 2016)
Based on color-magnitude diagrams (CMDs) from the Hubble Space Telescope Hubble Tarantula Treasury Project (HTTP) survey, we present the star formation history of Hodge 301, the oldest star cluster in the Tarantula Nebula. The HTTP photometry extends faint enough to reach, for the first time, the cluster pre-main sequence (PMS) turn-on, where the PMS joins the main sequence. Using the location of this feature, along with synthetic CMDs generated with the latest PARSEC models, we find that Hodge 301 is older than previously thought, with an age between 26.5 and 31.5 Myr. From this age, we also estimate that between 38 and 61 Type II supernovae exploded in the region. The same age is derived from the main sequence turn-off, whereas the age derived from the post-main sequence stars is younger and between 20 and 25 Myr. Other relevant parameters are a total stellar mass of ≈8800 ± 800 M ⊙ and average reddening E ( B − V ) ≈ 0.22-0.24 mag, with a differential reddening δE ( B − V ) ≈ 0.04 mag.